From Authoritarianism to Participatory Governance? A Legal and Constitutional Review of Public Participation in Indonesia’s Mineral and Coal Mining Laws - Muhamad Pelengkahu (Universitas Negeri Semarang, 2026)
This article critically examines the evolution of public participation in Indonesia’s mineral and coal mining legislation from the post‑independence era through the 2023 reforms. Drawing on a normative‑doctrinal methodology, it analyses four principal statutes (Law No. 11/1967, Law No. 4/2009, Law No. 3/2020 (as amended by the Law No. 6/2023)) alongside their derivative regulations. The study deploys Arnstein’s ladder of participation to assess the degree of meaningful engagement granted to affected communities, and integrates the Constitutional Court’s five‑function model of state resource control (beleid, bestuursdaad, regelendaad, beheersdaad, toezichthoudensdaad) and Ostrom’s collective‑action theory to contextualize normative shifts. Findings reveal that under the 1967 regime, public involvement was effectively absent, amounting to non‑participation. The 2009 Mining Act introduced tokenistic consultation and information‑sharing mechanisms without substantive influence. The 2020 amendments marked a shift toward partnership—granting formal channels for complaints, community development obligations, and limited consent procedures—yet persisted in privileging state and corporate prerogatives. The 2023 reforms further codified participatory requirements in area designation and social‑and‑environmental funding, but enforcement and procedural clarity remain uneven. The article concludes that while Indonesia’s mining laws reflect progressive normative commitments to public participation, significant gaps in implementation, transparency, and community empowerment persist. It recommends targeted regulatory guidance and stronger monitoring mechanisms to align statutory provisions with constitutional and international participatory standards.